Caraterísticas pós-abate de bovinos terminados com substitutos ao milho em dietas de alto grão - Cattelam, Jonatas (2015)
The objective of this study was to evaluate the characteristics of non-integrant parts of steers and heifers, feedlot fed with high-grain diets. Were used forty-five cattle were used in two categories, with 21 heifers with initial age of 32 months and 24 steers with initial age of 20 months, from the crossing between Charolais and Nellore. The animals were assigned to treatments as according energy source in the diet, being these: rice; white oat or corn, being seven heifers and eight bulls for each diet. The animals were confined until, by estimate, hot carcass weight of 220 kg. A complety randomized experimental design was completely randomized in 3 x 2 factorial arrangement (three food treatments and two categories). Slaughter weights were higher for cattle fed with white oat (449.3 kg) or corn (430.4 kg) compared to animals that receiving rice (401.8 kg), with higher carcass yields for animals than received corn. For the relationship between the empty body weight and slaughter weight of cattle also was no difference between the diets used and the major relationship was observed for animals that received corn (88.3%) compared to animals fed with rice (84.9%) or oat (84.1%). The exception of heart fat, in different forms of expression, and abomasal fat, expressed in relation to the empty body weight, for the remaining fat deposits, animals fed rice showed lower values. Regarding of animal category, the steers showed greater development of internal organs in different expression forms and legs and total of peripheral components, expression in relation to the empty body weight, while heifers showed higher weight for omasum and higher deposition in total fat. Weights and yields of commercial cuts sidecut and sawcut were higher for cattle fed with white oat or corn. For the forequarter weight and arm circumference, animals that received corn were higher than the animals that received rice, with intermediate behavior for cattle fed with white oat. Animals that received rice showed tenderness (5.15 points) and palatability (5.46 points) lower compared those were fed white oat (5.73 and 6.40 points, respectively) or corn (6.04 and 6.45 points, in the same order). According as the animal categories, steers showed higher percentage of forequarter (38.00 against 37.4%), while heifers showed greater carcass length (126.0 against 123.1 cm). The use of high-grain diets based on corn or white oat in finishing cattle results in a higher development of internal organs and the digestive tract, produce carcasses with higher weight and adequate fat deposition and with higher yields of commercial cuts, while feeding with rice produce lean meats, however reduces the carcass weight, with higher chilling loss and less tenderness meat. The production of heifers or steers feedlot finished ensures similar organleptic meat products.